Applying Instructional Design Technologies To Teach Stenography Online - Jawan, Baisah (2006)
The aim of this study is to produce a model to improve the preparation of lessons for teaching stenography online, particularly in the resources required by instructors. The model will be incorporated with the adopted techniques tested in a typical online course preparation.